How to restore endodontically treated posterior teeth: A conservative approach - Kantardžić Ivana; Blažić Larisa; Vasiljević Darko; Petrović Đorđe (Serbian Medical Society - Dental Section, Belgrade, 2012)
Reconstruction of endodontically treated teeth is common procedure in everyday clinical practice. It has great impact on prognosis of endodontically treated teeth, however, there is no consensus regarding the most predictable restorative procedure. Widely accepted procedure has included the use of post and core and crown. Nowadays, sound tooth structure preservation has become one of the most influencing factors in terms of survival rate of treated teeth. Therefore, direct restorations have become more advantageous as compared to crowns. This article is a review about conservative reconstruction of endodontically treated posterior teeth. The purpose was to give the guidelines for clinicians how to choose the most successful therapeutic procedure for each individual case.